Absence of endogenous interleukin 10 enhances early stress response during post-ischaemic injury in mice intestine. Issue 5 (1st May 2001) - Zingarelli, B; Yang, Z; Hake, P W; Denenberg, A; Wong, H R
Abstract : BACKGROUND: Interleukin 10 (IL-10) exerts a wide spectrum of regulatory activities in immune and inflammatory responses. AIMS: The aim of this study was to investigate the role of endogenous IL-10 on modulation of the early inflammatory response after splanchnic ischaemia and reperfusion. METHODS: Intestinal damage was induced by clamping the superior mesenteric artery and the coeliac trunk for 45 minutes followed by reperfusion in IL-10 deficient mice (IL-10 −/− ) and wild-type controls. RESULTS: IL-10 −/− mice experienced a higher rate of mortality and more severe tissue injury compared with wild-type mice subjected to ischaemia and reperfusion. Splanchnic injury was characterised by massive epithelial haemorrhagic necrosis, upregulation of P-selectin and intercellular adhesion molecule 1, and neutrophil infiltration. The degree of oxidative and nitrosative damage was significantly higher in IL-10 −/− mice than in wild-type littermates, as indicated by elevated malondialdehyde levels and formation of nitrotyrosine. Plasma levels of the proinflammatory cytokines tumour necrosis factor α and interleukin 6 were also greatly enhanced in comparison with wild-type mice. These events were preceded by increased immunostaining and activity of the stress regulated c-Jun NH2 terminal kinase and activation of the transcription factor activator protein 1 in the cellular nuclei of damaged tissue. CONCLUSIONS: These data demonstrate that endogenous IL-10 exerts an anti-inflammatory role during reperfusion injury, possibly by regulating early stress related genetic response, adhesion molecule expression, neutrophil recruitment, and subsequent cytokine and oxidant generation.